Integrated GIS and remote sensing tools approach for the management of peripheral areas in Maghreb cities from 1988-2005. Case study: Greater Agadir (Morocco) and the city of Algiers (Algeria) - Atik, Mohamed; Mahmoud Sebbab, Mohamed; Ousbih, Mehdi; El Ouahidi, Abdelhadi (Revista de Estudios Andaluces, 2025)
This paper aims to characterize the state of land use and its spatio-temporal evolution of the two representative sites: Greater Agadir (Morocco) and the eastern periphery of Algiers (Algeria). To fulfill this objective, we applied the supervised classifications and grid method on a series of satellite images, “Landsat-TM and ETM” from 1988-2005, and aerial photos and orthophotos. This processing is supported by surveys and field data. Then we produced maps to obtain quantitative data on the spatiotemporal evolution of land cover and the assessment of agricultural land consumption. We concluded that the study areas experienced poorly managed urbanization which has encroached on half of the agricultural area during the period 1987-2005 with the loss of more than 12,000 ha at a rate of 700 ha/year.